2020
DOI: 10.3390/cells9030712
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in the Nuclei of Rat Myocardial Cells

Abstract: Electron microscopic study of cardiomyocytes taken from healthy Wistar and OXYS rats and naked mole rats (Heterocephalus glaber) revealed mitochondria in nuclei that lacked part of the nuclear envelope. The direct interaction of mitochondria with nucleoplasm is shown. The statistical analysis of the occurrence of mitochondria in cardiomyocyte nuclei showed that the percentage of nuclei with mitochondria was roughly around 1%, and did not show age and species dependency. Confocal microscopy of normal rat cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Intranuclear mitochondria have occasionally been reported in several cell types, including cardiac myocytes [25,26], but the incidence and details regarding the specific mechanism whereby mitochondria appear in the nuclear matrix are unknown. In this study, we did not find any mitochondria inside the nucleus; only we found this organelle in the perinuclear area.…”
Section: Discussionmentioning
confidence: 99%
“…Intranuclear mitochondria have occasionally been reported in several cell types, including cardiac myocytes [25,26], but the incidence and details regarding the specific mechanism whereby mitochondria appear in the nuclear matrix are unknown. In this study, we did not find any mitochondria inside the nucleus; only we found this organelle in the perinuclear area.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of organelle such as mitochondria has also been observed after NE repair, questioning the fate and consequence of such an intruder on nuclear dynamics [ 69 ]. Interestingly, 1% of rat cardiomyocytes, a cell type that endures persistent mechanostress, present mitochondria in their nucleus, giving more importance to this phenomenon [ 121 ].…”
Section: Chromosomal Instability Associated To Nedmentioning
confidence: 99%
“…The anatomical and functional connection between mitochondria and the nucleus provides a coordinated cellular response to intracellular changes. The study by Eldarov et al [12] explored the idea that mitochondria interaction with the nucleus is beyond intramembrane connection; it espouses the notion that a tiny fraction of the organelle could reside in the nucleus. This provocative concept has its genesis from earlier studies, but the results at the time generated skepticisms.…”
Section: Mitochondria In Healthmentioning
confidence: 99%